Effect of TiO2 on the electrical properties of hexanoyl chitosan LiClO4 based polymer electrolyte / Mohamad Ridzuan Ahmad - Ahmad, Mohamad Ridzuan (2010)
Hexanoyl chitosan-LiClO4-TiO2 electrolyte system was prepared by solution cast technique. The ionic conductivity for the Hexanoyl chitosan-LiClO4-TiO2 was conducted over a wide range of frequency and at temperatures between 283 and 333 K. Dielectric data were analyzed using complex permittivity ε* and complex electrical modulus M* for the sample with the highest ionic conductivity at various temperatures. Within the temperature range investigated, the conductivity of the hexanoyl chitosan-LiClO4-TiO2 based system are thermally assisted and can be described by Arrhenius law indicating that the conductivity of polymer electrolyte increase with the increasing of temperature. This indicated that the salt undergoes greater dissociation as the temperature increase.